The gender factor in the perception of English segments by non-native speakers - Bryła-Cruz, Agnieszka (Studies in Second Language Learning and Teaching, 2021)
The aim of the paper is to present the findings of an empirical study which contributes to the ongoing research into gender effects on second language acquisition by exploring a biological influence on L2 pronunciation learning. One of the most frequent arguments used to vindicate single-sex education is that there are substantial sensory and perceptual differences between males and females which rationalize gender-specific teaching methods and gender-segregation at schools. The present study provides some preliminary insights into the perception of selected phonetic contrasts by Polish secondary school learners with the aim of investigating gender-based similarities and differences in the accuracy of sound recognition by males and females. The findings suggest that a commonly cited female advantage in acquiring L2 pronunciation cannot be attributed to their superior phonetic perception, as male participants performed equally well and identified the same number of English segments correctly.